Design and Empirical Evaluation of an Agile Web Engineering Process - Sampaio, Américo; Vasconcelos, Alexandre; Sampaio, Pedro R. Falcone (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2004)
Web applications present important characteristics that must be properly addressed by software engineering methods, processes and techniques. In most cases, Web systems have to be delivered complying with severe time constraints due to its strategic nature for the client’s business. In this work we describe an agile process for Web-based application development, XWebProcess, which is based on Extreme Programming and aims at building high quality Web applications in a time effective way. The process is described using the SPEM meta-modeling language to facilitate its understanding and further improvements. An experiment was conducted to assess the time effectiveness and the quality of the proposed process. The results have shown that XWebProcess is equally agile when compared to Extreme Programming, moreover, surveys conducted as part of the experiment pointed out that XWebProcess is suitable to Web development in dimensions such as requirements gathering, user interface and navigation design, and software testing.